Effects of anabolic steroids on acute phase responses in intra-abdominal sepsis - K. Mealy; A. Clooney; P. Marks; T. Hennessy; J. Jackson (Hindawi Limited, 1997)
The acute phase response is an important adaptive response to sepsis and injury. As anabolic steroids increase protein synthesis we postulated that these agents might also increase hepatic acute phase protein synthesis. Male Wistar rats were pretreated with testosterone or danazol for 48 h prior to caecal ligation and puncture (CLP). Thirty-six h following surgery the animals were killed and blood taken for full blood count, total protein, albumin, α, β and γ globulin fractions on serum electrophoresis, complement C3 and transferrin levels. Danazol increased the α1, α2 and β1 globulin serum protein fractions in comparison with no surgery and CLP alone groups. These results indicate that danazol increases plasma acute phase proteins, as measured by electrophoresis, in this model of intra-abdominal sepsis.